2022
DOI: 10.1002/lio2.829
|View full text |Cite
|
Sign up to set email alerts
|

A novel MPZL2 c.68delC variant is associated with progressive hearing loss in Chinese population and literature review

Abstract: Objective: The aim of this study was to identify genetic etiology in two unrelated Chinese probands with progressive sensorineural hearing loss.Methods: Two unrelated Chinese families were recruited. Genetic etiology was identified by targeted next-generation sequencing (NGS) and verified by Sanger sequencing. Hearing evaluations included pure tone audiometry, auditory brainstem response to clicks, and otoscopic examination. Medical history and computerized tomography scan of temporal bone were also collected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…By comparing the hearing level at the rst consultation and follow-up, we observed that 35.71% (10/28) patients had reduced hearing; however, the progression of HL could not be determined in 2 patients (patients no.34 and 35) in this study. The rate of HL was 2.10 and 13.33 dBHL per year in patient nos.30 and 37, respectively, which is higher than that reported in the literature (0.59 dBHL/year) [15]. A total of 64.29% (18/28) of patients did not report reduced hearing.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…By comparing the hearing level at the rst consultation and follow-up, we observed that 35.71% (10/28) patients had reduced hearing; however, the progression of HL could not be determined in 2 patients (patients no.34 and 35) in this study. The rate of HL was 2.10 and 13.33 dBHL per year in patient nos.30 and 37, respectively, which is higher than that reported in the literature (0.59 dBHL/year) [15]. A total of 64.29% (18/28) of patients did not report reduced hearing.…”
Section: Discussioncontrasting
confidence: 60%
“…Moreover, the Mpzl2 mutant mice showed early-onset progressive HL and a signi cantly increased ABR threshold [5], which was similar to the ndings in human. However, the rate of HL development in the Mpzl2 mutant mice was much faster than that in humans, and the HL in Mpzl2 mutant mice rapidly developed to moderate and severe at 8 and 12 weeks, respectively (ABR threshold higher than 70 dB SPL) [5,15]. To better demonstrated the extent of HL caused by MPZL2 variants, we combined our results with those from previous studies (a total of 39 cases in Table 1) to comprehensively analyze the genotype and phenotype correlation of the MPZL2 variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Pro23-Leufs*2) and c.463del,p. (Ala155Leufs*10) truncating variants have each been reported in the compound heterozygous state with one of the recurrent variants or in the homozygous state in three individuals (Table 1) (Kim et al, 2020;Wang et al, 2022). Finally, a missense variant of uncertain significance, c.52C>T,p.…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies on DFNB111 have mainly focused on the Dutch, Moroccan, and some Middle Eastern countries [ 8 , 14 , 15 ]. In East Asia countries such as Korea [ 4 , 16 ] and China [ 17 ], only a few families were identified with these defects and to date, no systematic phenotype-genotype correlation analysis for MPZL2 has been performed.…”
Section: Introductionmentioning
confidence: 99%